Rasa Lokal Rejeki Internasional: “Betul, Betul, Betul" Aspek Ekonomi Politik dalam Kartun Animasi Upin & Ipin - Aloysius Ranggabumi Nuswantoro (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
TV program is value laden. There were backgrounds, business strategy, political interest, etc which is called Political Economy of Media. Analysis to Political economy of media will show the facts/interest behind the program. In the other side, public has right to know and to inform the information clearly even the background. Upin & Ipin is popular cartoon animation for Malaysian even Indonesian. It is value laden of civics, ethnicity, capital and also culture infiltration. Upin & Ipin apply the concept of commodification, spasialization and structurazion successfully based on Malaysia value. Upin & Ipin is the real strength not only to Malaysia even the near country.